Skarifikasi Benih Sengon (Falcataria moluccana) Menggunakan Aplikasi Kombinasi Perendaman Air Panas dan Air dingin pada Media Tanam Pasir - Ogandy, Bintang Zwari; Marlina, Marlina; Harun, M.Umar; Kurnianingsih, Astuti (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2024)
Ogandy, B. Z., Marlina, M., Harun, M. U., Kurnianingsih, A. (2024). Scarification of sengon (Falcataria moluccana) seeds using hot and cold water soaking combination application on sand planting media. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 623–633). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Scarification is a process done to break the dormancy and accelerate the process of water absorption in seed germination. The purpose of the study was to determine the most effective hot and cold water scarification methods on Sengon (Paraserianthes moluccana.) seed germination. In this experiment, a completely randomized design was used, with six treatments of soaking Sengon seeds in hot and cold water, with four replications, there were 24 units, with 20 seeds per unit.The total number of seeds was 480. Seed soaking, consisting of : soaked in 60℃ hot water for four minutes and then soaked in cold water for 12 hours (P1), soaked in 60℃ hot water for five minutes and then soaked in cold water for 12 hours (P2), soaked in 80℃ hot water for four minutes and then soaked in cold water for 12 hours (P3), soaked in 80℃ hot water for five minutes after that soaked in cold water for 12 hours (P4), soaked in 100℃ hot water for four minutes after that soaked in cold water for 12 hours (P5), soaked in 100℃ hot water for five minutes after that soaked in cold water for 12 hours (P6). The results showed that the dry weight of sprouts in soaking Sengon seeds in 100°C hot water for five minutes after that soaked in cold water for 12 hours was significant in sprout dry weight.